Strategies for measuring prescription medication switching with pharmacy claims data: a scoping review protocol. Issue 9 (11th September 2021) - Harris, Daniel A.; Bouck, Zachary; Tricco, Andrea C.; Cadarette, Suzanne M.; Iaboni, Andrea; Bronskill, Susan E.
ABSTRACT: Objective: This scoping review will aim to compare strategies for measuring prescription medication switching with pharmacy claims data, with a focus on psychotropic vs non-psychotropic medications. Introduction: Medication switching (ie, the replacement of one medication for another) is common and occurs due to several factors (such as adverse effects to a specific medication). In pharmacoepidemiology studies that use pharmacy claims data, it is important to identify and account for switches; however, due to data limitations and lack of a methodological standard, this can be challenging. The aim of this scoping review is to describe how studies have previously measured medication switching with pharmacy claims data in order to create a repository of common strategies and highlight areas for future research. Inclusion criteria: This review will include studies that have used pharmacy claims data to measure medication switching as their primary independent or dependent variable. Studies conducted at the individual level (ie, not ecological), published between January 1, 1980, and October 31, 2020, and investigating orally administered, non-anti-infective medications will be considered. No age, population, or context restrictions are specified as inclusion criteria. Methods: JBI methodology and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews were used for this protocol. MEDLINE (PubMed), Embase (Ovid), Central (Cochrane Library), CINAHL (EBSCO), and Google Scholar will be searched with the assistance of a health sciences research librarian. Two reviewers will independently screen titles, abstracts, and full-text articles. Strategies for measuring medication switching will be narratively described and summarized overall and by broad medication class.